Landslide Hazards, Public Intervention and Property Values – The Case of Saguenay, Quebec, Canada - Des Rosiers, François; Tossou, Bienvenu (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2024)
Since the beginning of the 21st century, over 100 major landslides have been reported worldwide, which resulted in both human casualties and massive damages to property. While the academic and technical literature on landslide hazard risk assessment is quite abundant, relatively few studies address the issue of the impact of landslide exposure on property values. In this research, we look at the impact that public intervention aimed at compensating homeowners affected by landslide hazard constraint zones had on residential values in La Baie, an arrondissement of the City of Saguenay (formerly Chicoutimi), in the province of Quebec, Canada. The area was most affected by the Saguenay flood that hit the region on July 19 and 20, 1996 and which was followed by a series of landslides. A difference-in-differences (DiD) spatial hedonic price model is estimated using a representative sample of 813 single-family sales transacted in La Baie between 2009 and 2016. Findings suggest that, caeteris paribus, and nearly two decades after the 1996 events, the compensation scheme implemented at the local level in December 2012 did not manage to completely offset the disadvantages of building constraints on high-risk sites induced by the new regulations and translated into a statistically significant price discount of 3.4% for affected properties as opposed to unaffected ones. They also suggest that a panoramic view on the Saguenay fjord adds some 8.6% to a property’s value.